The implication of intellectual capital and profitability on firm value - Elizabeth Hutami Widowati; Eka Bertuah (Enrichment : Journal of Management, 2023)
This study aims to determine the effect of intellectual capital and profitability on firm value. This research can provide information about factors that can increase firm value in the midst of intense global competition, especially consumption companies that require a good image in the eyes of consumers. Intellectual capital in this study is measured by the VAIC formula, while profitability uses the ROE proxy, and firm value is measured by the TOBINSQ. There were 61 company samples and 305 observational data were obtained with a range of research years from 2017 – 2021. This study used a panel data regression model using stata research tools and the most powerful model, namely Command Effect model. The regression results show that VAIC has effect on TOBINSQ but not significant, and ROE has a significant positive effect on TOBINSQ.